ANALISIS MANAJEMEN KELAS PEMBELAJARAN PENDIDIKAN AGAMA BUDDHA DI SMP - Budi Tri Apriyanto; Dwiyono Putranto; Novianti Novianti (Jurnal Muara Pendidikan, 2023)
The teacher plays an important role they are responsible for classroom management. Teachers must be able to create a conducive teaching and learning so that the teaching and learning process takes place properly and effectively. Based on observations at Kaloran 1 Public Middle School, Buddhist teachers said they did not understand class management and some students said that they just attend but not pay attention to their teachers. This is because the class is not comfortable, the classroom is not too wide, the teacher often uses old method. This study aims to determine the implementation of classroom management that has been carried out and the obstacles that exist in implementing management classes in class VII Buddhist studies at SMP Negeri 1 Kaloran. The research method used is qualitative by using data collection techniques through observation, interviews, and documentation. The results of this study indicate that the implementation of classroom management in teaching Buddhism has implemented learning planning, learning arrangements, leading classes, controlling, and evaluating learning. However, there are still obstacles in the implementation process, such as teachers also teach in other schools so that when the time of implementation of learning sometimes clashes, this makes learning not optimal, and the infrastructure is lacking, such as classrooms that are not spacious.